Use of Social Media to Instigate Violence: Users’ Role and Challenges in Prevention - Naher, Jibon; Minar, Matiur Rahman (Technium Social Sciences Journal, 2023)
In Bangladesh, there have been many incidents of violence linked to social media platforms, particularly Facebook. These incidents have been caused by posts that have either intentionally or unintentionally provoked hatred and instigated violence. In this study, we examine seven such incidents that were triggered by religious differences in Bangladesh. By reviewing previous research and case studies, we aim to identify the factors that contribute to the spread of hate speech and misinformation on social media. We also discuss the challenges involved in preventing violent incidents. To reduce the likelihood of such incidents, we propose three recommendations: prioritize news for fact-checking, promote fact-checking among users, and involve users in the fact-checking process. These recommendations can be implemented using existing technology to limit the spread of false information and hate speech on social media platforms. This could ultimately reduce the risk of violent incidents triggered by social media.